Analisis Efektifitas Pola Rekrutmen Kader Rantingmuhammadiyah Di Ponorogo - Robby Darwis Nasution (Universitas Muhammadiyah Ponorogo, 2018)
professional resources that can support all kinds of vision, mission or goals of the organization. To get members who have a high professionalism of course required a good recruitment and not just random, because how many members of an organization would be meaningless if not have adequate competence. Conversely, if an organization, although having few members but in each member has adequate competence, then the rate of development of the organization will run well then it is important that large organizations such as Muhammadiyah looking for the right pattern in recruitment cadres in order to support organizational performance. Furthermore, in this research will use descriptive qualitative research method by taking samples from three twigs in Ponorogo regency which represents the central city area, the central area and the periphery. The conclusion this research is recruitment pattern owned by the Muhammadiyah organization is Muhammadiyah educational institution, employee charity Muhamamdiyah, and the general public and there is no direct recruitment process.Orientation or encouragement of prospective members to participate in Muhammadiyah organization other than it is as a medium of learning and means of worship (non-profit oriented). This is very different from the existing recruitment theory where recruitment theory in general is on profit oriented organizations or companies.